DIFFICULTIES IN TEACHING READING TO YOUNG LEARNERS - Umaralieva Munojat Mashrabovna; Obidova Shoxistaxon Nuridinjon qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: This article explores the challenges that teachers face when working with young students in educational settings. The abstract provides an overview of the key issues discussed in the article, including the unique characteristics of young learners, such as their limited attention spans and varying levels of cognitive development. The article also examines strategies that teachers can use to address these difficulties and create a positive learning environment for young students. Overall, the article highlights the importance of understanding the specific needs of young learners and adapting teaching methods to effectively engage and support their learning.